2018
DOI: 10.3390/rs10111807
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Ground-Based Measurements of Aerosol Optical Depth over Kuwait City

Abstract: We analyze ten years (2008–2017) of ground-based observations of the Aerosol Optical Depth (AOD) in the atmosphere of Kuwait City, in Middle East. The measurements were conducted with a CIMEL sun-sky photometer, at various wavelengths. The daily average AOD at 500 nm (AOD500) is 0.45, while the mean Ångström coefficient (AE), calculated from the pair of wavelengths 440 and 870 nm, is 0.61. The observed high AOD500 values (0.75–2.91), are due to regional sand and dust storm events, which are affecting Kuwait wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 50 publications
(28 reference statements)
1
10
0
Order By: Relevance
“…The downward shortwave profile shows reductions from 200 to 800 W m −2 , which scales with the trend in average dust amounts. The shortwave reductions by dust of ∼ 200-250 W m −2 for the Ginoux and Walker simulations are similar to those shown by Slingo et al (2006) and Kosmopoulos et al (2017) for corresponding dust AOD in the range of 1.5-2.5. These reductions by themselves would tend to induce a cooling ef-fect near the ground during the daytime by limiting the landsurface heating.…”
Section: Daytime Radiative Fluxessupporting
confidence: 79%
See 1 more Smart Citation
“…The downward shortwave profile shows reductions from 200 to 800 W m −2 , which scales with the trend in average dust amounts. The shortwave reductions by dust of ∼ 200-250 W m −2 for the Ginoux and Walker simulations are similar to those shown by Slingo et al (2006) and Kosmopoulos et al (2017) for corresponding dust AOD in the range of 1.5-2.5. These reductions by themselves would tend to induce a cooling ef-fect near the ground during the daytime by limiting the landsurface heating.…”
Section: Daytime Radiative Fluxessupporting
confidence: 79%
“…They are known to strongly influence the radiation budget due to their significant scattering and absorption properties (Carlson and Benjamin, 1980;Kinne et al, 2003;Sokolik and Toon, 1996;Dubovik et al, 2006). Dust aerosol layers can contribute to low-level atmospheric cooling due to the attenuation of shortwave radiation (solar dimming) through both scattering and absorption at solar wavelengths (Carlson and Caverly, 1977;Tegen and Lacis, 1996;Slingo et al, 2006;Lau and Kim, 2007;Kosmopoulos et al, 2017). Solar dimming can also lead to reduced surface heating and thus reduced latent and sensible heat fluxes (Wang et al, 2004;Prakash et al, 2015).…”
mentioning
confidence: 99%
“…Summer is from May until August. During June and July, north-westerly winds may develop, generating extensive dust storms [25]. Autumn starts from the month of September and is characterized by winds switching from the southeast to the northwest.…”
Section: Study Areamentioning
confidence: 99%
“…The results revealed that the elevated values of AOD from 0.75 to 2.91 are because of dust episodes, which are affecting Kuwait with an annual average frequency of about 20 days per year. The backward trajectories of air masses showed the elevated main source areas of dust affecting Kuwait significantly originated from Saudi Arabia with the contribution of the 56% and other source areas from Iraq and Iran that the contribution of 21% to the mean annual AOD [43]. Pi et al [27] indicated considerable spatial variability of dust storm frequencies in the Xinjiang Province in northwest China, where the annual mean number of dusty days was 111.3 in the south and 10.9 in the north.…”
Section: Discussionmentioning
confidence: 99%